2014
DOI: 10.1111/bcpt.12307
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Cabergoline and Bromocriptine on Metabolic and Cardiovascular Risk Factors in Patients with Elevated Prolactin Levels

Abstract: Hyperprolactinaemia is suggested to be associated with metabolic and hormonal complications. No previous study has compared the effect of different dopamine agonists on plasma lipids, carbohydrate metabolism markers and cardiovascular risk factors in patients with elevated prolactin levels. The study included eight bromocriptine-resistant women with prolactinoma (group 1) and twelve matched women with hyperprolactinaemia unrelated to prolactinoma (group 2). Group 1 was then treated with cabergoline, while grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 34 publications
6
31
2
1
Order By: Relevance
“…Although lipid levels slightly correlated with plasma levels of extralipid markers assessed in our study, differences in baseline concentrations of uric acid, hsCRP, homocysteine, and fibrinogen do not seem to result from dyslipidemia because all groups of patients were characterized by similar levels of plasma lipids. Interestingly, previously we found that both bromocriptine and cabergoline reduced circulating levels of cardiovascular risk factors, but the effect of cabergoline, which is a more potent prolactin‐lowering agent than bromocriptine, was stronger . These findings and the results of our current study may suggest that oligosymptomatic or asymptomatic women with hyperprolactinemia should be treated with dopamine agonists to reduce cardiometabolic risk.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although lipid levels slightly correlated with plasma levels of extralipid markers assessed in our study, differences in baseline concentrations of uric acid, hsCRP, homocysteine, and fibrinogen do not seem to result from dyslipidemia because all groups of patients were characterized by similar levels of plasma lipids. Interestingly, previously we found that both bromocriptine and cabergoline reduced circulating levels of cardiovascular risk factors, but the effect of cabergoline, which is a more potent prolactin‐lowering agent than bromocriptine, was stronger . These findings and the results of our current study may suggest that oligosymptomatic or asymptomatic women with hyperprolactinemia should be treated with dopamine agonists to reduce cardiometabolic risk.…”
Section: Discussionsupporting
confidence: 68%
“…Interestingly, previously we found that both bromocriptine and cabergoline reduced circulating levels of cardiovascular risk factors, but the effect of cabergoline, which is a more potent prolactin-lowering agent than bromocriptine, was stronger. 29 These findings and the results of our current study may suggest that oligosymptomatic or asymptomatic women with hyperprolactinemia should be treated with dopamine agonists to reduce cardiometabolic risk. From a cardiometabolic point of view, dopaminergic agents are better drugs than those used by some symptomatic women with hyperprolactinemia oral contraceptive pills, which were found to increase circulating levels of cardiometabolic risk factors.…”
Section: Discussionsupporting
confidence: 67%
“…In turn, our patients were included only if total and LDL cholesterol levels were elevated and many of them had glucose metabolism abnormalities. For this reason and because pleiotropic effects of dopamine receptors agonists partially correlated with the effects on plasma prolactin [19], it may be assumed that concentrations of the assessed biomarkers would be lower than in our study if participants received higher doses of bromocriptine, stronger reducing plasma prolactin. Importantly, plasma levels of the investigated variables were similar to those found in prolactin-matched women receiving chronic metformin therapy.…”
Section: Discussionmentioning
confidence: 70%
“…Beyond lowering fasting [16][17][18] and postchallenge [10] plasma glucose, which was accompanied by an improvement in insulin sensitivity [16,[18][19][20][21] and a decrease in glycated hemoglobin [18], dopamine agonists reduced plasma lipids [16,18,19], body mass index [22,23], waist circumference [24], visceral adiposity [18,21], circulating levels of cardiometabolic risk factors [18][19][20]25], and the prevalence of metabolic syndrome [21]. These cardiometabolic effects of dopamine agonists depended on dose [18] but were only partially associated with the effect of treatment on circulating prolactin levels [19]. They may partially explain why in a long-term, randomized, double-blind trial, quick-release bromocriptine, in addition to their usual diabetes therapy, led to a reduction in the composite cardiovascular endpoint by 42% [26].…”
Section: Introductionmentioning
confidence: 99%
“…A hyperprolactinaemia nemcsak a menstruációt és a peteérést befolyásolja, hanem a szénhidrát-és a lipidanyagcserére is kedvezőtlen hatása van. Mind a bromocriptin, mind a Magyarországon nem forgalmazott cabergolin kedvező-en csökkenti a prolaktinszintet és a HOMA-IR-t, de a cabergolin kedvezőbb a többi cardiovascularis rizikófak-tor -IGF-1, FFA, húgysav, hsCRP, homocisztein, fi brinogén, HDL-C, 25(OH)D -szempontjából [24]. A cabergolin nem cukorbeteg elhízottaknál csökkenti az inzulin-és a vércukorszintet [25].…”
Section: Bromocriptin Cabergolinunclassified